Sorption technology for obtaining uranium from technogenic and hydromineral raw materials using natural modified sorbents - Abdualiyev Б.Б.; Satanova Б.М.; Abuova Ф.У.; Aralbayeva Г.М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
This work is devoted to the study of sorption technology for obtaining uranium from technogenic and hydromineral raw materials using natural modified sorbents. The main purpose of the study is to determine the effectiveness and prospects of this technology in the field of uranium mining and processing. The paper analyzes various types of naturally modified sorbents, their sorption capacity and the specificity of uranium. Special attention is paid to the environmental aspects of this technology, since the use of natural modified sorbents minimizes the negative impact on the environment. The paper also discusses methods of recovery and reuse of sorbents, which contributes to the resource efficiency of this technology. The economic benefits of the use of sorption technology are also considered in the work, taking into account the reduction of costs for the extraction and processing of uranium. The results of the study show that the sorption technology for producing uranium using naturally modified sorbents has high efficiency and prospects for industrial applications. The need for further research and innovation in this area is noted in order to improve processes and develop new types of sorbents. The work is of practical and scientific value for specialists in the field of mining and environmental safety, and can also be used as a basis for further research and development in this area.